Existing Laws to Combat Road Traffic Injury in Nepal and Bangladesh: A Review on Cross Country Perspective - Shafiq, Shafina; Dahal, Sushma; Siddiquee, Noor Kutubul Alam; Dhimal, Meghnath; Jha, Anjani Kumar (Journal of Nepal Health Research Council, 2020)
Background: Road traffic accidents is a leading cause of injury and death globally. The consequences of road traffic accidents are prominent in developing countries that can least afford to meet the health services, economic and societal challenges. Nepal and Bangladesh are two developing country of South Asia who bear a large share of burden due to road traffic injuries. Methods: A non-systematic review of relevant documents using Google scholar and PubMed as well as review of relevant legal documents was done. Results: Nepal and Bangladesh have traffic laws including all the key risk factors as recommended by the World Health Organization except the child restraint systems laws. The existing laws for both countries include speed, drunk driving, use of seatbelts and motorcycle helmet, driver license, vehicle condition, overloading and accident related compensations.In both the countries for post-crash response, national emergency care access number has partial coverage and in Nepal there are some provisions related to trauma registry.Vulnerable groups are pedestrians with majority of male and higher mortality found in rural areas than urban areas for both the countries. Conclusions: Both the countries have traffic laws that focus on the prevention of road traffic accidents and protection of victims. However, amendments in the existing laws are required for confronting immediate challenges of increasing accidents and injuries that both the countries face every year. Keywords: Bangladesh; Nepal; road traffic injury; road traffic accident; traffic acts and laws.